2015
DOI: 10.1515/cclm-2014-0183
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of adult T-cell leukemia/lymphoma cells using simple four-color flow cytometry

Abstract: Our newly established method quantified tumor cells in patients with acute-type ATL. Furthermore, this method was useful for assessing the efficacy of chemotherapy, and the change of the CD7N proportion could be more important to predict prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…HAS Flow method has been established, showing that the proportion of TSLC1 + subpopulations (TSLC1 pos CD7 dim and TSLC1 pos CD7 neg ) increased with the progression from AC to indolent and to aggressive ATL. This analysis identified the putative high risk AC and also the intermediate stage of ATL progression 51 , 52 . In the present study, ALA-PDT successfully induced 98.7% of ATL leukemic cell death with minimal damage on the healthy PBMCs in chronic ATL patient specimen, implying that ALA-PDT effectively inhibit the progression from indolent to aggressive ATL in addition to identification of intermediate stage of progression in ATL (Figs 5 and 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…HAS Flow method has been established, showing that the proportion of TSLC1 + subpopulations (TSLC1 pos CD7 dim and TSLC1 pos CD7 neg ) increased with the progression from AC to indolent and to aggressive ATL. This analysis identified the putative high risk AC and also the intermediate stage of ATL progression 51 , 52 . In the present study, ALA-PDT successfully induced 98.7% of ATL leukemic cell death with minimal damage on the healthy PBMCs in chronic ATL patient specimen, implying that ALA-PDT effectively inhibit the progression from indolent to aggressive ATL in addition to identification of intermediate stage of progression in ATL (Figs 5 and 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…The serum levels of soluble interleukin‐2 receptor (sIL‐2R) were collected from medical records. The percentages of abnormal lymphocytes in white blood cells were counted microscopically by clinical laboratory technicians as previously described . The HTLV‐1 PVL data were obtained from the Joint Study on Predisposing Factors of ATL Development (JSPFAD) .…”
Section: Methodsmentioning
confidence: 99%
“…Clinically, ATL is characterized by high frequency of skin rashes. In most cases, circulating tumor cells in this disease are characterized by CD4 + CD7 − immunophenotypes (Ishigaki et al, 2015). Therefore, the clinical course of this disease can be followed by the monitoring of the proportion of CD4 + CD7 − T cells (Ishigaki et al, 2015).…”
Section: Adult T-cell Leukemia/lymphoma (Atl)mentioning
confidence: 99%
“…In most cases, circulating tumor cells in this disease are characterized by CD4 + CD7 − immunophenotypes (Ishigaki et al, 2015). Therefore, the clinical course of this disease can be followed by the monitoring of the proportion of CD4 + CD7 − T cells (Ishigaki et al, 2015). In addition, it was reported that the number of CD3 dim CD4 + CD7 low were increased significantly in acute-type ATL.…”
Section: Adult T-cell Leukemia/lymphoma (Atl)mentioning
confidence: 99%
See 1 more Smart Citation